1997
DOI: 10.1016/s0140-6736(97)05487-1
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial of systemic methotrexate versus laparoscopic salpingostomy in tubal pregnancy

Abstract: General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
117
2
18

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(144 citation statements)
references
References 18 publications
(12 reference statements)
7
117
2
18
Order By: Relevance
“…By analysing the tubal preservation, we did not find a statistically significant difference in the preservation of the fallopian tubes in women who received salpingostomy 45/49 (91.8%) compared to women who received medical treatment with systemic methotrexate 46/51 (90.2%) MTX [14]. The same study also examined the ipsilateral tubal patency, showing 23/39 (59%) of patent ipsilateral tubes in women who received surgical treatment and 23/42 (54.8%) for women who received medical treatment with systemic methotrexate.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…By analysing the tubal preservation, we did not find a statistically significant difference in the preservation of the fallopian tubes in women who received salpingostomy 45/49 (91.8%) compared to women who received medical treatment with systemic methotrexate 46/51 (90.2%) MTX [14]. The same study also examined the ipsilateral tubal patency, showing 23/39 (59%) of patent ipsilateral tubes in women who received surgical treatment and 23/42 (54.8%) for women who received medical treatment with systemic methotrexate.…”
Section: Discussionmentioning
confidence: 64%
“…Among the analysed studies, five trials were conducted in the US, two in Egypt and France and the others in Finland, Iran, New Zealand, Sweden, Netherlands and the United Kingdom. Comparing systemic methotrexate treatment in multiple dose regimen and laparoscopic salpingostomy, a multicentre study found a nonsignificant trend toward greater success of drug treatment [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent intrauterine pregnancy rates were 83.5 and 81%, respectively [13]. Another randomised trial comparing systemic methotrexate or laparoscopic salpingostomy demonstrated comparable ipsilateral tubal patency rates (55 vs 59%) [14].…”
Section: Medical Management Of Tubal Ectopic Pregnancymentioning
confidence: 97%
“…La finalidad de preservar la integridad tubárica es a costa de un mayor riesgo de trofoblasto persistente, definido como concentraciones séricas de β-HCG en aumento o estables después del tratamiento conservador inicial, para el cual se requiere un tratamiento adicional (quirúrgico o médico) (7)(8)(9)(10)(11).…”
Section: Introductionunclassified